Lipid and polyunsaturated fatty acid contents in infant formulas in reference to the Codex Alimentarius - Mahyara Markievicz Mancio Kus-Yamashita; Sabria Aued-Pimentel; Jorge Mancini Filho (Fundação Oswaldo Cruz (FIOCRUZ), 2016)
Codex Alimentarius stan-72 (2011) discriminate the adequate values of fatty acids and lipids for infant formula. Total lipids and polyunsaturated fatty acids were quantified in fourteen infant formulas samples and compared the results with the recommended values. Extraction and quantification of lipids followed Roese Gottielb method. Analysis of fatty acid, methylated by Hartman and Lago procedure, was carried out through gas chromatography was performed with the use of internal standard 23:0. In the analyzed samples, at least one parameter was in disagreement with Codex Alimentarius.